P62 Impact of the Covid-19 pandemic on the SeaSHeL study - Joshi, Nikhil (BJS Open, 2021)
INTRODUCTION: The SeaSHeL Study is an ongoing national, multi-centre, cohort study investigating Sudden Sensorineural Hearing Loss (SSNHL). The study is supported by the INTEGRATE ENT Trainee Research Network and the Audiology NIHR Champions, as well as being adopted onto the NIHR Clinical Research Network. It aims to map the pathway of patients with SSNHL, develop a prognostic model to predict recovery of patients with idiopathic SSNHL and establish the impact on patients’ quality of life. Here we summarise the impact of the Covid-19 pandemic on the study and highlight methods employed to improve data collection. METHODS: Data collection commenced in October 2019 and as of August 2020, 227 patients have been recruited from 66 registered sites across England. This interim data was analysed. The primary outcome was the change in monthly patient recruitment and site registration. The secondary outcome was the completeness of the dataset. RESULTS: Initially, monthly site registration increased to a peak of 31 in December 2019 and monthly patient recruitment increased to a peak of 34 in February 2020. Both levels decreased during the first wave of Covid-19 with 11 patients recruited and 0 sites registered in April 2020. Both levels have been increasing since, with 21 patients recruited and 5 sites registered in August 2020. The dataset of 227 patients has 113 (49.7%) completed records. CONCLUSIONS: This study represents the largest national cohort study into SSNHL. Despite the Covid-19 pandemic, data collection continued during the first wave and rates are now recovering to pre-Covid-19 levels. Key factors in this recovery are a collaborative research approach involving motivated trainees, an ethics amendment for follow-up data to be collected by telephone and continued engagement of collaborators through regular email correspondence and fortnightly newsletters.